An Analysis of The Exclusion and Inclusion Processes of Reynhard Sinaga Case’s in Tribunnews.Com - Simanullang, Rikki; Pangaribuan, Rotua (The Explora, 2021)
The purpose of this study is to find out how are the exclusion and inclusion processes of Reynhard Sinaga case in Tribunnews.com.This study used a qualitative descriptive method with the approach of critical discourse analysis from Theo van Leeuwen to describe how the social actors are portrayed in the news. The source of data of this study was taken from 10 Reynhard Sinaga’s news in a Tribunnews.com. dated the February 1th to February 30th, 2020. There are ninety data in Reynhard Sinaga's news containing Exclusion and Inclusion processes. The finding of this research were found three strategies of Exclusion process in the Reynhard Sinaga’s news namely Passivation, Nominalization and Substitution of clause and seven strategies of Inclusion process, namely Differentiation - Indifferentiation, Objectivation - Abstraction, Nomination - Categorization, Nomination - Identification, Determination - Indetermination, Assimilation Individualization, Association - Dissociation. The most dominant strategy of Exclusion process found is Passivation with 9%, and for the most dominant strategies of Inclusion process found are objectivation – abstraction and determination - indetermination with 23%. The writer would like to offer the suggestion to students of English department to enrich their knowledge in understanding the process of exclusion and inclusion when writing, to lecturer, for teaching materials for students in order to better understand the use of the Exclusion & Inclusion process strategy and its effects and journalists, and news writers to be able to write news accurately and with certainty without eliminating one of the social actors and presenting social actors as they are so as not to have a negative effect on readers and society.